2022
DOI: 10.33795/jraam.v6i1.009
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pengelolaan Keuangan Desa Berbasis Kearifan Lokal

Abstract: Tanggal masuk : 24-10-2021 This study seeks to reveal the meaning and manifestation of the value of kamalamputan in village financial management. This research is in the realm of a qualitative paradigm with ethnography as the knife of analysis. Data was collected using depth interview techniques, participant observation and documentation. The method of data analysis used Spradley's ethnographic analysis technique. This study found that the value of kamalamputan was accepted as the value of honesty that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The findings show that local wisdom has the ability to reduce the possibility of fraudulent practices in village fund management. [12] revealed that the values of local wisdom of kamalamputan were adopted as the principle of honesty and then reapplied in the daily activities of the people of Lembang Village, especially in village financial management. [13] It was found that the financial management system is inseparable from the principle of local wisdom in the demen, which is able to survive thanks to a strong social framework.…”
Section: An Investigation By Indonesiamentioning
confidence: 99%
“…The findings show that local wisdom has the ability to reduce the possibility of fraudulent practices in village fund management. [12] revealed that the values of local wisdom of kamalamputan were adopted as the principle of honesty and then reapplied in the daily activities of the people of Lembang Village, especially in village financial management. [13] It was found that the financial management system is inseparable from the principle of local wisdom in the demen, which is able to survive thanks to a strong social framework.…”
Section: An Investigation By Indonesiamentioning
confidence: 99%